Development of the insulin secretion mechanism in fetal and neonatal rat pancreatic B-cells: response to glucose, K+, theophylline, and carbamylcholine - Mendonça, A.C.; Carneiro, E.M. [UNESP]; Bosqueiro, J.R. [UNESP]; Crepaldi-Alves, S.C. [UNESP]; Boschero, A.C. (Associação Brasileira de Divulgação Científica (ABRADIC), 1998)
We studied the development of the insulin secretion mechanism in the pancreas of fetal (19- and 21-day-old), neonatal (3-day-old), and adult (90-day-old) rats in response to stimulation with 8.3 or 16.7 mM glucose, 30 mM K+, 5 mM theophylline (Theo) and 200 µM carbamylcholine (Cch). No effect of glucose or high K+ was observed on the pancreas from 19-day-old fetuses, whereas Theo and Cch significantly increased insulin secretion at this age (82 and 127% above basal levels, respectively). High K+ also failed to alter the insulin secretion in the pancreas from 21-day-old fetuses, whereas 8.3 mM and 16.7 mM glucose significantly stimulated insulin release by 41 and 54% above basal levels, respectively. Similar results were obtained with Theo and Cch. A more marked effect of glucose on insulin secretion was observed in the pancreas of 3-day-old rats, reaching 84 and 179% above basal levels with 8.3 mM and 16.7 mM glucose, respectively. At this age, both Theo and Cch increased insulin secretion to close to two-times basal levels. In islets from adult rats, 8.3 mM and 16.7 mM glucose, Theo, and Cch increased the insulin release by 104, 193, 318 and 396% above basal levels, respectively. These data indicate that pancreatic B-cells from 19-day-old fetuses were already sensitive to stimuli that use either cAMP or IP3 and DAG as second messengers, but insensitive to stimuli such as glucose and high K+ that induce membrane depolarization. The greater effect of glucose on insulin secretion during the neonatal period indicates that this period is crucial for the maturation of the glucose-sensing mechanism in B-cells.
Keywords: rat islet cell; glucose; pancreatic islets; carbamylcholine; theophylline; potassium; insulin secretion